\(x^2+y^2=x+y+8\)
\(\Leftrightarrow4x^2-4x+1+4y^2-4y+1=34\)
\(\Leftrightarrow\left(2x-1\right)^2+\left(2y-1\right)^2=34\)
Đơn giản rồi nhé
Đúng 0
Bình luận (0)
Em có cách này tuy nhiên không chắc.
Viết lại phương trình với x là ẩn:
\(x^2-x+\left(y^2-y-8\right)=0\) (1)
Để phương trình (1) có nghiệm thì \(\Delta=\left(-1\right)^2-4\left(y^2-y-8\right)\ge0\)
\(\Leftrightarrow-4y^2+4y+33\ge0\Leftrightarrow\frac{1-\sqrt{34}}{2}\le y\le\frac{1+\sqrt{34}}{2}\)
Mà \(y\inℕ\Rightarrow0\le y\le3\)
....
Đúng 0
Bình luận (0)